2023
DOI: 10.1002/hsr2.1304
|View full text |Cite
|
Sign up to set email alerts
|

The burden of ocular morbidities among elderly patients visiting a district healthcare facility in Malawi: A retrospective study

Abstract: Background: The population of older adults is growing dramatically. Sadly, this populace is highly prone to develop various ocular morbidities, which if left unattended can lead to blindness.Aim: To determine the distribution of ocular morbidities among older adults at a secondary hospital in Malawi.Methods: This was a retrospective cross-sectional study conducted at Mzimba North District Hospital in Malawi. We retrieved 314 patient records from the hospital's ophthalmic outpatient registry from August 2020 to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
2

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 26 publications
0
5
2
Order By: Relevance
“…In the current study, prevalence of eye diseases was higher in the month of June and peaked in July which is contrary to the study conducted at Mzimba, Malawi where the highest number was recorded in March 12 . The high frequency of eye conditions in this month in our study coincides with the winter season in Malawi and also represents off season for various farming activities hence majority has time to attend to eye health care 31 .…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In the current study, prevalence of eye diseases was higher in the month of June and peaked in July which is contrary to the study conducted at Mzimba, Malawi where the highest number was recorded in March 12 . The high frequency of eye conditions in this month in our study coincides with the winter season in Malawi and also represents off season for various farming activities hence majority has time to attend to eye health care 31 .…”
Section: Discussioncontrasting
confidence: 99%
“…In this review, more males than females had ocular morbidities similar to the pattern observed among general population in the central region at Kasungu, Malawi and in Eastern Odisha, India respectively 15 , 16 . In contrast, a study conducted at a district health facility in Mzimba district in Northern Malawi found that females visit eye care facilities more than their male counterparts 12 . The variation could be attributed to different eye care services offered at the district and tertiary level.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Although eye care services are provided freely at the point of access as part of the Essential Health Package, Malawians still incur transportation costs. 30 Therefore, this study highlights the role of outreach eye screening programs in high-risk population groups. 31 , 32…”
Section: Discussionmentioning
confidence: 84%
“…10 The pattern of ocular disease varies from country to country and even in the same country from district to district. 11 Previous studies have assessed the distribution of eye diseases at government hospitals, 8,12,13 however, there is no baseline data on the pattern of ocular morbidity among the Malawian elderly visiting nongovernment facilities. In Malawi, health services are provided for free at government facilities while private for-profit and private nonprofit organizations charge fees.…”
mentioning
confidence: 99%